GIS-based calculation method to predict mining subsidence in flat and inclined mining: A comparative case study - Djamaluddin, Ibrahim; Indrayani, Poppy; Cai, Yue; Jiang, Yujing (Journal of the Civil Engineering Forum, 2024)
Prediction of ground movements in the case of continuous subsidence is critically important for the planning of underground mining. Many calculation models are used to predict mining subsidence. A comprehensive method to render current calculation models superfluous can only come from a theoretical model, but the challenge remains in defining the parameters, given the great variety of rock structures found. Hence, innovation through a conceptual and technological study of the subsidence mechanism is needed to ensure that this problem can be solved satisfactorily. In this study, a new method is proposed to predict ground surface subsidence by combining a stochastic medium concept with Geographic Information System (GIS) technology. All subsidence computations are implemented within GIS, where spatial components are used to conduct the subsidence prediction analysis. This paper includes simulations of basic subsidence phenomena and a comparative study of the GIS-based calculation method’s suitability against the empirical method from the Subsidence Engineer Handbook (SEH), semi-empirical influence function models, and numerical modeling. First, the influence of basic extraction area categories on the character of mining subsidence at the surface for flat seam layers is verified. Second, subsidence and horizontal displacement profiles are compared for both gently and steeply inclined mining. Finally, the verification of calculated horizontal strain values for an actual case of inclined irregular mining is also conducted. The comparative results of subsidence predictions for flat and gently sloping mining demonstrate the suitability of the GIS-based calculation method for use in underground mining strategy.